Macroeconomic determinants of economic growth: Empirical validation on the case of African countries - Gafsi, Nesrine; Bakari, Sayef (International Journal of Innovative Research and Scientific Studies, 2025)
Economic growth remains a critical objective for African countries, given the continent’s unique developmental challenges and opportunities. This study investigates the macroeconomic determinants of economic growth in 54 African countries over the period 1999–2023, employing a comprehensive panel data approach. By analyzing a wide range of variables—including domestic investment, labor force dynamics, trade openness, urbanization, financial development, energy use, consumption, digitalization, and natural resource rents—the study provides a holistic understanding of the drivers of economic growth in Africa. The findings reveal that domestic investment, final consumption expenditure, and exports are the most significant drivers of growth, underscoring the importance of capital accumulation, domestic demand, and trade in fostering economic expansion. However, the study also highlights challenges related to import dependency, weak labor force contributions, and the limited impact of financial development, urbanization, and digitalization. Additionally, the positive association between carbon dioxide emissions and growth raises important questions about the trade-offs between economic development and environmental sustainability. The study concludes with policy recommendations tailored to the African context, emphasizing the need for investment in infrastructure, human capital, and technology, as well as sustainable development and regional integration. By adopting a nuanced and context-specific approach to economic policy, African countries can unlock their growth potential and achieve sustainable and inclusive development.